HOW CAN PSYCHOLOGY AND RELIGIOUS BELIEFS AFFECT ON FRAUD TRIANGLE? - Bassem Ismail; Hamidah Hamidah (Media Riset Akuntansi, Auditing & Informasi, 2019)
In this paper, I explore the emphasis of the fraud triangle as a salutary model for practitioner to extract fraud. This paper is anchored through psychology and religious theories, and is propped with prove from holy books. The findings point out that the Own lust “Hawa Nafsu” (HN) supporter and basic stone to control devil desire (DD) that control by humans lust that’s present new model in preventing fraud. Fraud is a manifold phenomenon, whose religious theories may not fit all the cases into fixed model. Thus, fraud tringle not adequately credible model, so antifraud practitioner should consider fraud from religious perspective. The study uses secondary sources of information get it from magazine articles, textbooks and the Internet. The discussion of the two theories contributes to understand frauds especially by legitimate accountants, auditors, fraudsters and other fraudulent entities. The study also serves as a guide to further research on fraud.